10 - Mafeje and Langa: The Start of an Intellectual’s Journey - Sharp, John (Africa Development, 2021)
Drawing on material in the Wilson papers in the University of Cape Town ar- chives, this article reviews the contribution Archie Mafeje made to Monica Wilson’s research project in Langa (Cape Town, South Africa) in the early 1960s. It also discusses the character of the relationship between Wilson and Mafeje that emerged in the course of his contribution to the project, showing how a warm and respectful relationship was sustained through the difficult period of the late 1960s, and into the 1970s when Mafeje reformulated his arguments relating to Langa and his assessment of liberal, ‘assimilationist’ South African anthropology. The article concludes by drawing out some of the wider implica- tions of this episode of intellectual history, seeking to contextualise the antipa- thy towards anthropology that Mafeje expressed in later years.